Energetic response of Atlantic surfclam Spisula solidissima to ocean acidification. (December 2020) - Pousse, Emilien; Poach, Matthew E.; Redman, Dylan H.; Sennefelder, George; White, Lauren E.; Lindsay, Jessica M.; Munroe, Daphne; Hart, Deborah; Hennen, Daniel; Dixon, Mark S.; Li, Yaqin; Wikfors, Gary H.; et al.
Abstract: In this study, we assessed the Atlantic surfclam ( Spisula solidissima ) energy budget under different ocean acidification conditions (OA). During 12 weeks, 126 individuals were maintained at three different ρCO2 concentrations. Every two weeks, individuals were sampled for physiological measurements and scope for growth (SFG). In the high ρCO2 treatment, clearance rate decreased and excretion rate increased relative to the low ρCO2 treatment, resulting in reduced SFG. Moreover, oxygen:nitrogen (O:N) excretion ratio dropped, suggesting that a switch in metabolic strategy occurred. The medium ρCO2 treatment had no significant effects upon SFG; however, metabolic loss increased, suggesting a rise in energy expenditure. In addition, a significant increase in food selection efficiency was observed in the medium treatment, which could be a compensatory reaction to the metabolic over-costs. Results showed that surfclams are particularly sensitive to OA; however, the different compensatory mechanisms observed indicate that they are capable of some temporary resilience. Highlights: Surfclam energy budget is decreased by high ρCO2 concentration. High ρCO2 concentration affects negatively surfclam clearance rate. Surfclams adopt different metabolic strategies facing ocean acidification. Metabolic loss rises after a moderate ρCO2 concentration increase.